Los registros administrativos y la toma de decisiones en la Gerencia Sub Regional de Ucayali Contamana 2023 - Soria Guevara, David Alfredo (2024)
This study was carried out with the purpose of determining the relationship between administrative records and decision making in the Sub Regional Management of Ucayali, Contamana 2023. The study was applied, descriptive - correlational level with non-experimental design, taking 130 as a population workers to whom a questionnaire of questions was used to collect information and data. The results obtained indicate that the administrative records are classified as regular (46%); while decision making is regular with 47%. Subsequently, correlations were obtained where there is a positive and significant relationship between administrative records and decision making, demonstrated by a coefficient of 0.819 and significance of 0.000. Likewise, the strategic decisions dimension shows a coefficient and significance of r=0.882; p=0.000 being positive; Likewise, the tactical decision shows a coefficient and significance of r=0.787; p=0.000 which qualifies as strong positive; Finally, operational decisions have a coefficient and bilateral significance of r=0.566; p= 0.000, all of them are significantly related to administrative records.